Ear stones in crocodylians: a cross-species comparative and ontogenetic survey of otolith structures - Schwab, Julia A. (2022)
The vestibular system of the inner ear is a crucial sensory organ, involved in the sensation of balance and equilibrium. It consists of three semicircular canals that sense angular rotations of the head and the vestibule that detects linear acceleration and gravity. The vestibule often contains structures, known as the otoliths or ' ear stones'. Otoliths are present in many vertebrates and are particularly well known from the fossil record of fish, but surprisingly have not been described in detail in most tetrapods, living or extinct. Here, we present for the first time a survey of the otoliths of a broad sample of extant crocodylian species, based on computed tomography scans. We find that otoliths are present in numerous crocodylian species of different growth stages, and they continue to increase in size during ontogeny, with positive allometry compared to skull length. Our results confirm that otoliths are a common component of the crocodylian vestibular system, and suggest they play an important role in sensory detection. Otoliths are likely common, but overlooked, constituents of the inner ear in tetrapods, and a broader study of their size, shape and distribution promises insight into sensory abilities.